Capturing Sensitive Information from Difficult-to-Reach Populations : Evidence from a Novel Internet-Based Survey in Yemen - Tandon, Sharad; Vishwanath, Tara (World Bank, Washington, DC, 2022)
As conflicts across the globe escalate and data collection in these settings becomes more sensitive, policy makers and researchers are forced to turn to alternative methods for accurately collecting vital information. This paper assesses the ability of novel and anonymous internet-based surveys to elicit sensitive information in the Republic of Yemen's conflict by comparing identical sensitive and non-sensitive questions in an internet survey to a concurrent mobile phone survey. There were significant differences between the modalities in all the sensitive questions, with a greater share of respondents expressing sensitive views in the internet survey. The differences between modalities was larger for sensitive questions than for non-sensitive questions, and all the differences were qualitatively identical for subsets of the sample that are underrepresented in internet surveys. Overall, the results suggest that internet surveys can be an effective tool to use in conjunction with other techniques to acquire information that would otherwise be difficult to collect.